2016
DOI: 10.1016/j.ibiod.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Industrial-scale culturing of the crude oil-degrading marine Acinetobacter sp. strain HC8-3S

Abstract: a b s t r a c tThe marine bacterium Acinetobacter sp. strain HC8-3S, capable of degrading petroleum hydrocarbons, was previously shown to be applicable for bioremediation. Here, we evaluated the performance of the strain during industrial-scale fermentation, long-term storage, and biodegradation processes. Fermentation parameters were optimized for industrial-scale culturing using lower salinity and fewer inorganic salts in the culture medium. The shelf-life of the fermentation broth was evaluated in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…HC8-3S (GenBank accession number MN216306), which were both isolated from the crude oil-contaminated marine sediments of Bohai Bay, China. Detailed information about these two strains in crude oil utilization could also be found in our previous study (Lin et al, 2014;Liu et al, 2016;Chen et al, 2017).…”
Section: Bacteria Crude Oil Media and Chemicalsmentioning
confidence: 91%
“…HC8-3S (GenBank accession number MN216306), which were both isolated from the crude oil-contaminated marine sediments of Bohai Bay, China. Detailed information about these two strains in crude oil utilization could also be found in our previous study (Lin et al, 2014;Liu et al, 2016;Chen et al, 2017).…”
Section: Bacteria Crude Oil Media and Chemicalsmentioning
confidence: 91%
“…Acinetobacter sp. strains are most often found in contaminated habitats [3] and act as the best degraders for the bioremediation of soil polluted by crude oil [14]. The marine crude oil-degrading bacterium Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…The marine crude oil-degrading bacterium Acinetobacter sp. strains have been cultured on an industrial scale [14]. Study on the multiple catabolic capacity of 31 isolates belonging to the genus Acinetobacter has shown multiple degradation of hydrocarbons, dibenzothiophene, fluorene, dibenzofuran, benzyl sulfide, and sodium benzoate [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 1:4 diluted seawater could increase 10% biomass of Bacillus thuringiensis in 72 hour at 30°C (Ghribi et al, 2007). In addition, crude oil-degrading bacteria isolated from sediment could grow in variety concentration of salt from 10 to 30 g/L (Liu et al, 2016). This bacterial strain entered to stationary phase after 9 hours in 15% SB medium with diluted and non-diluted seawater.…”
Section: Effect Of Seawater Concentration and Sugarcane Molasses Conc...mentioning
confidence: 94%